Neurotoxic Anatoxin-a Can Also Exert Immunotoxicity by the Induction of Apoptosis on Carassius auratus Lymphocytes in vitro When Exposed to Environmentally Relevant Concentrations - Zhong, Yuchi; Shen, Lilai; Ye, Xueping; Zhou, Dongren; He, Yunyi; Li, Yan; Ding, Ying; Zhu, Weiqin; Ding, Jiafeng; Zhang, Hangjun (Frontiers in Physiology, 2020)
Hazardous anatoxin-a (ANTX-a) is produced by freshwater algal blooms worldwide, which greatly increases the risk of consumer exposure. Although ANTX-a shows widespread neurotoxicity in aquatic animals, little is known about its mechanism of action and biotransformation in biological systems, especially in immunobiological models. In this study, transmission electron microscopy results showed that ANTX-a can destroy lymphocytes of C. auratus in vitro by inducing cytoplasmic concentration, vacuolation, and swollen mitochondria. DNA fragmentations clearly showed a ladder pattern in agarose gel electrophoresis, which demonstrated that the apoptosis of fish lymphocytes was caused by exposure to ANTX-a. Flow cytometry results showed that the apoptotic percentage of fish lymphocytes exposed to 0.01, 0.1, 1, and 10 mg/L of ANTX-a for 12 h reached 18.89%, 22.89%, 39.23%, and 35.58%, respectively. ANTX-a exposure induced a significant increase in reactive oxygen species (ROS) and malonaldehyde (MDA) in lymphocytes, a decrease in the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), a reduction in the glutathione (GSH) content, and an inactivation of glutathione reductase (GR), glutathione peroxidase (GPx), and glutathione-s-transferase (GST). Although these observations were dose-dependent, these results suggested that ANTX-a can induce lymphocyte apoptosis via intracellular oxidative stress and destroy the antioxidant system after a short exposure time of only 12 h. Besides neurotoxicity, ANTX-a may also be toxic to the immune system of fish, even when the fish are exposed to environmentally relevant concentrations, which clearly demonstrated that the potential health risks induced by ANTX-a in aquatic organisms requires attention.